Mucosa‐Like Conformal Hydrogel Coating for Aqueous Lubrication - Bai, Meng‐Han; Zhao, Baisong; Liu, Zhou‐Yun‐Tong; Zheng, Zi‐Li; Wei, Xin; Li, Lingli; Li, Ka; Song, Xingrong; Xu, Jia‐Zhuang; Li, Zhong‐Ming (Advanced materials (Weinheim), 2022)
Mucosa is a protective and lubricating barrier in biological tissue, which has a great clinical inspiration because of its slippery, soft, and hydrophilic surface. However, mimicking mucosal traits on complex surface remains an enormous challenge. Herein, a novel approach to create mucosa‐like conformal hydrogel coating is developed. A thin conformal hydrogel layer mimicking the epithelial layer is obtained by first absorbing micelles, followed by forming covalent interlinks with the polymer substrate via interface‐initiated hydrogel polymerization. The resulting coating exhibits uniform thickness (≈15 µm), mucosa‐matched compliance (Young's modulus = 1.1 ± 0.1 kPa) and lubrication (coefficients of friction = 0.018 ± 0.003), robust interfacial bonding against peeling (peeling strength = 1218.0 ± 187.9 J m–2), as well as high water absorption capacity. It effectively resists adhesion of proteins and bacteria without compromising biocompatibility. As demonstrated by an in vivo cynomolgus monkey model and clinical trial, applications of the mucosa‐like conformal hydrogel coating on the endotracheal tube significantly reduce intubation‐related complications, such as invasive stimuli, mucosal lesions, laryngeal edema, inflammation, and postoperative pain. This work offers a promising prototype for surface decoration of biomedical devices and holds great prospects for clinical translation to enable interventional operations with minimally invasive impacts. An ingenious yet feasible method of creating a mucosa‐like conformal hydrogel coating, which is soft, lubricative, hydrophilic, antifouling, biocompatible, and stable, is reported. This coating effectively reduces intubation‐related complications. This work represents a breakthrough to endow interventional medical devices with required surface properties, showing promising prospects for clinical translation.